Hydrogen‐bond network and pH sensitivity in human transthyretin. (1st October 2013) - Yokoyama, Takeshi; Mizuguchi, Mineyuki; Nabeshima, Yuko; Kusaka, Katsuhiro; Yamada, Taro; Hosoya, Takaaki; Ohhara, Takashi; Kurihara, Kazuo; Tanaka, Ichiro; Niimura, Nobuo
<x xml:space="preserve">Abstract</x> Transthyretin (TTR) is a tetrameric protein. TTR misfolding and aggregation are associated with human amyloid diseases. Dissociation of the TTR tetramer is believed to be the rate‐limiting step in the amyloid fibril formation cascade. Low pH is known to promote dissociation into monomer and the formation of amyloid fibrils. In order to reveal the molecular mechanisms underlying pH sensitivity and structural stabilities of TTR, neutron diffraction studies were conducted using the IBARAKI Biological Crystal Diffractometer with the time‐of‐flight method. Crystals for the neutron diffraction experiments were grown up to 2.5 mm3 for four months. The neutron crystal structure solved at 2.0 Å revealed the protonation states of His88 and the detailed hydrogen‐bond network depending on the protonation states of His88. This hydrogen‐bond network is involved in monomer–monomer and dimer–dimer interactions, suggesting that the double protonation of His88 by acidification breaks the hydrogen‐bond network and causes the destabilization of the TTR tetramer. Structural comparison with the X‐ray crystal structure at acidic pH identified the three amino acid residues responsible for the pH sensitivity of TTR. Our neutron model provides insights into the molecular stability related to amyloidosis.